Convergence Analysis of Parallel S-Iteration Process for System of Generalized Variational Inequalities. (12th October 2017) - Sahu, D. R.; Kang, Shin Min; Kumar, Ajeet
Abstract : We consider a new system of generalized variational inequalities (SGVI) defined on two closed convex subsets of a real Hilbert space. To find the solution of considered SGVI, a parallel Mann iteration process and a parallel S -iteration process have been proposed and the strong convergence of the sequences generated by these parallel iteration processes is discussed. Numerical example illustrates that the proposed parallel S -iteration process has an advantage over parallel Mann iteration process in computing altering points of some mappings.